2011
DOI: 10.1159/000330793
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Results of Photodynamic Therapy Combined with Intravitreal Anti-Vascular Endothelial Growth Factor for Polypoidal Choroidal Vasculopathy

Abstract: Background/Aims: To evaluate the 2-year efficacy of photodynamic therapy (PDT) combined with intravitreal injection of anti-vascular endothelial growth factor (anti-VEGF) in patients with polypoidal choroidal vasculopathy (PCV). Methods: Twenty-two eyes of 22 patients with PCV followed up for ≧24 months after PDT and anti-VEGF combination therapy were retrospectively reviewed. The patients received intravitreal anti-VEGF (1.25 mg bevacizumab or 0.5 mg ranibizumab) within 7 days after PDT. Eyes were retreated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…In these studies, significant improvement of visual acuity was obtained in the first year; however, treatment efficacy was decreased in year 2 15,16. Our study on combined PDT and IVR treatment showed similar results to combined PDT with intravitreal bevacizumab injection.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In these studies, significant improvement of visual acuity was obtained in the first year; however, treatment efficacy was decreased in year 2 15,16. Our study on combined PDT and IVR treatment showed similar results to combined PDT with intravitreal bevacizumab injection.…”
Section: Discussionsupporting
confidence: 66%
“…However, little information is available regarding the long-term efficacy of this combination. In the 2-year results for the combination of PDT and intravitreal bevacizumab injection, regression of the treatment effect was reported in year 2 15,16. For PDT with intravitreal injection of ranibizumab (IVR), follow-up time was limited to only one year;17,18 hence, long-term results for combination of PDT with IVR are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] However, in our institution, it was difficult to compare these patients because recurrent patients of combined therapy were changed into IVR monotherapy within 2 years. Although combined therapy could be also the main therapeutic choice in the present, Kim et al 29 described that the benefit of combined therapy diminished in year 2 with no significant difference compared with baseline. Further investigations are needed to compare combined therapy and IVR monotherapy during the long follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…135 Vision in eyes with recurrence after previous verteporfin PDT therapy stabilized but did not improve: a finding supported by the small study by Romano et al 130 The need for determining how to maximize the durability of the benefits of combination therapy is highlighted by findings that benefits in visual acuity after 1 year were substantially diminished at 2 years (mean BCVA: 0.43 ± 0.33 [baseline], 0.28 ± 0.24 [12 months], and 0.39 ± 0.28 [24 months]), with mean retreatment rates of 36.4% and 77.3% in the first and second years, respectively. 116 Recent genetic studies have demonstrated an association between genotype and outcomes in the treatment of PCV. 110,127,134 Clinical response to verteporfin PDT has differed significantly between patients with different variants of the SERPINF1 gene, which encodes pigment epithelium-derived factor.…”
Section: Direct Thermal Laser Photocoagulation Still Hasmentioning
confidence: 99%